Presenting the structural model of organizational silence based on leadership styles and organizational justice - Mazaheri, Sanaz (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2022)
Background and purpose: Today, human capital is considered the most important capital of the organization, and managers, knowing the importance and role of this capital, are trying to create a competitive advantage for their organization; The current research was conducted to provide a structural model of organizational silence based on leadership styles and organizational justice in the Islamic Azad University of Tehran. Methodology: This research is of an applied, descriptive-correlation type and the statistical population of this research included all the employees of the Islamic Azad University of Tehran in 2015-2016, which is 8021 people, using the Krejcie and Morgan table, 367 People were selected by cluster random sampling method. To collect data, Vakola and  Bouradas's (2005) organizational silence questionnaire, Bass and Olive's (1997) multifactorial leadership style, and Niehoff and Moorman's (1998) organizational justice were used. Structural equation modeling has been used for data analysis. Results: The results showed that exchange and transformational leadership style positively and significantly predicts non-interventional leadership style negatively organizational silence, organizational justice positively and significantly predicts organizational silence, and organizational justice the relationship between non-interventional leadership style. Moreover, it mediates organizational silence in a negative way and the relationship between transformational leadership style and transactional leadership style and organizational silence in a positive and meaningful way. Conclusion: The research results provide a model of effective factors on organizational silence based on leadership styles and organizational justice.